Analysis of the Quality of Bottled Drinking Water Products through a Six Sigma Approach and Failure Mode and Effect Analysis (FMEA): (Case Studies: PT XYZ) - Fimahali, Ahmad Yusuf; Sumiati, Sumiati (Journal of Applied Science, Engineering, Technology, and Education, 2023)
PT XYZ is a company engaged in Bottled Drinking Water (AMDK) with the brand "Santri" and has been operating since 1997. The raw materials used come from the Umbulan spring located in Mulyorejo hamlet, Pasuruan regency, East Java which is famous for its clarity. The results of the interview with the company, PT XYZ currently has not implemented quality control methods. Currently the quality of AMDK products PT XYZ has not been maximized, this is shown by the number of defective products that are greater than the established standards. Products with a packaging size of 240 ml are products with the highest percentage of defects. To overcome this problem, the Define, Measure, Analyze, Improve, and Control (DMAIC) approach is used in Six Sigma which is able to reduce defects and also with the FMEA method. Calculation with the Six Sigma method, there has been an increase in Sigma Level after improvement. Meanwhile, analysis using the FMEA method found that the RPN value decreased after the recommendations were implemented. This can be seen from the RPN value at the control stage is smaller than the RPN at the Analyze stage, thus showing the success of the corrective actions that have been taken.